Latinas and Latinos on TV : colorblind comedy in the post-racial network era - Molina-Guzmán, Isabel (Latinx pop culture., 2018)
"Interweaving discussions about the ethnic, racial, and linguistic representations of Latinas/os within network television comedies, Isabel Molina-Guzmán probes published interviews with producers and textual examples from hit programs like Modern Family, The Office, and Scrubs to understand how these primetime sitcoms communicate difference in the United States. Understanding the complex ways that audiences interpret these programs, Molina-Guzmán situates her analysis within the Obama era, a period when ethnicity and race became increasingly grounded in hipster racism, and argues that despite increased inclusion, the feel-good imperative of TV comedies still inevitably leaves racism, sexism, and homophobia uncontested"--Back cover